Can tax rate increases foster investment under entry and exit flexibility? Insights from an economic experiment - René Fahr; Elmar Janssen; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
It is well-known that taxes affect risky investment decisions. Analytical studies indicate that tax rate increases can foster (accelerate) investment if there is flexibility, in particular when an exit option is available. We design an experiment that is based on an analytical model with binomial random walk and entry and exit flexibility. Contrasting the underlying model, we find accelerated investment, which is often considered as an increased willingness to invest, on tax rate increases to be independent of the existence of an exit option. However, we observe this investor reaction only for a tax increase, not for a tax decrease. This investment behavior is driven possibly by tax salience and the mechanisms known from the theory of irreversible choice under uncertainty. Our empirical evidence suggests that the accelerating tax effects are much more common than is predicted by the theoretical literature. Policy makers should therefore carefully consider the behavioral aspects when anticipating taxpayer reactions.
Keywords: H25; H21; C91; 330; Investment Decisions; Tax Effects; Timing Flexibility; Economic Experiment